10 minute guide to Excel 97 - Fulton, Jennifer (Que, 1997)
10 minutes is all you need to learn how to create and customize your own toolbar; enter different types of data: numbers, dates, times, and more; create and save workbook files; add columns, rows, headers, and footers; perform calculations with formulas and functions; use styles to format cells; add cell borders and shading; and save Excel data in on the Internet or an intranet.